PERFORMANCE OF NURSES IMPLEMENTING IN PATIENT ROOM BAGAS WARAS KLATEN HOSPITAL - Ernitasari Darmastuti; Sudarwati Sudarwati; Ida Ariyati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This is a quantitative study aimed at determining the degree of influence and significance of competency characteristics, work motivation, work experience, and work environment on the performance of nurses working in Bagas Waras Klaten Hospital. The population in this study was the managing nurse in the Bagas Waras Klaten Hospital's hospital room, which had a total of 116 people. The model used in this study was an implementing nurse in the hospital room of Bagas Waras Klaten Hospital who met specific criteria set. Based on the requirements set, the sample in this study amounted to 85 implementing nurses in the hospital room bagas Waras Klaten Hospital Multiple linear regression tests done with SPSS software are among the data analysis approaches employed by statistical analysis. Based on the findings of hypothesis testing and discussions, it can be concluded that competence, work experience, work motivation, and work environment all have a beneficial impact on Bagas Waras Klaten Hospital nurses' performance. Keywords: Competence, Work Motivation, Work Experience, Work Environment, Nurse Performance.